Understanding Coke Deposition Vis-à-Vis DRM Activity over Magnesia-Alumina Supported Ni-Fe, Ni-Co, Ni-Ce, and Ni-Sr Catalysts - Yousef M. Alanazi; Naitik Patel; Anis H. Fakeeha; Jehad Abu-Dahrieh; Ahmed A. Ibrahim; Ahmed E. Abasaeed; Rawesh Kumar; Ahmed Al-Fatesh (Nanomaterials, 2023)
The catalytic conversion of CH4 and CO2 into H2-rich syngas is known as the dry reforming of methane (DRM). The dissociation of CH4 over active sites, coupled with the oxidation or polymerization of CH4−x (x = 1–4), plays a crucial role in determining in determining the DRM product yield and coke deposition. Herein, a series of bimetallic-supported catalysts are prepared by the dispersion of Ni-M (M = Ce, Co, Fe, and Sr) over 60 wt% MgO-40 wt% Al2O3 (60Mg40Al) support. Catalysts are tested for DRM and characterized with XRD, surface area and porosity, temperature-programmed reduction/desorption, UV−VIS−Raman spectroscopy, and thermogravimetry. 2.5Ni2.5Sr/60Mg40Al and 2.5Ni2.5Fe/60Mg40Al, and 2.5Ni2.5Ce/60Mg40Al and 2.5Ni2.5Co/60Mg40Al have similar CO2 interaction profiles. The 2.5Ni2.5Sr/60Mg40Al catalyst nurtures inert-type coke, whereas 2.5Ni2.5Fe/60Mg40Al accelerates the deposition of huge coke, which results in catalytic inferiority. The higher activity over 2.5Ni2.5Ce/60Mg40Al is due to the instant lattice oxygen-endowing capacity for oxidizing coke. Retaining a high DRM activity (54% H2-yield) up to 24 h even against a huge coke deposition (weight loss 46%) over 2.5Ni2.5Co/60Mg40Al is due to the timely diffusion of coke far from the active sites or the mounting of active sites over the carbon nanotube.